Synthesis and characterization of thermoresponsive ZIF-8@PNIPAm- co -MAA microgel composites with enhanced performance as an adsorption/release platform - Allegretto, Juan Alejandro (2019)
Composite materials featuring a synergic combination of interesting properties such as stimuli responsiveness and tailored porosity are highly appealing due to their multiple possible applications. We hereby present an example which brings together such features by using poly(N-isopropyl-acrylamide)-derived thermo-responsive microgels and Zn-based Metal Organic Framework (MOF) ZIF-8, capable of selective adsorption. Such a composite was obtained by including methacrylic acid as a co-monomer in the microgel, in order to position carboxylic acid moieties within the polymeric matrix, which via preconcentration of MOF precursors would trigger confined heterogeneous nucleation. The highly integrated composite obtained features thermoresponsivity and permanent porosity. Methylene blue adsorption/desorption experiments were performed, revealing a dramatic enhancement of its cargo capacity together with an increased release efficiency.